(untitled) (GYMNASIUM, 2017)
In this paper the authors deal with the obesity of the Czech female population. As a basic criterion for the evaluation of obesity, several standard parameters used worldwide were selected. These include the body mass index (BMI), %body fat, and the “fitness score”. For the inclusion among the female obese population, these following threshold parameters were chosen: BMI ≥ 25 kg/m2, fitness score (FS) ≤ 70 points, body fat (%) ≥ 30. The research sample consisted of 319 women divided into 6 age groups. The results show that in the studied women (p <0.05) BMI increases with increasing age. For example, the percentage of women who fall into the category of overweight or obese according to BMI is 16.7% in the age group 18 – 29 years, 25.8% in the group 30 – 39 years, 32.7% in the group 40 – 49 years, 45.5% in the group 50-59 years, 66.0% in the group 60-69 years, and 85.7% in the group 70+ years. The percentage of fat increases with increasing age as well. The fitness score starts to drop since the age of 50 years and slightly rises in the age groups 30 – 39 and 40 - 49.